Carbon and Nitrogen dynamics in flooded soils (International Rice Research Institute (IRRI), 2000)
The book identified soil carbon and nitrogen dynamics as a key area for future research and recommended that a program of strategic research be mounted in collaboration with centers of excellence worldwide.